Asymptotic solution of acoustic nonlinear wave equation with friction - K. WERNEROWSKI (Archives of Acoustics)
A contribution to the development of asymptotic method of small parameter was made and applied to the analysis of the propagation of nonlinear acoustic waves. The result is close to strict empiric function. Asymptotic solution of acoustic nonlinear wave equation with friction was found. The result enables the propagation velocity and the pressure of an acoustic wave to be evaluated.